x-1 + x-3 = x+13
x+5 x+2
If someone could do this step by step would help me a ton and would be appreciated.
I am confused about the LCD is it LCD=(x+5),(x+2)?
because when I do on the right side of the = it is (x+13)(x+5)(x+2) and I think thats wrong because she said in our class we wont foil three sets of brackets.
the LCD is (x+5)(x+2)
if you mulitply ech term by the LCD you will eliminate the fractions and have (x-1)(x+2)+(x-3)(x+5)=(x+13)(x+5)(x+2)
FOIL the 1st and 2nd terms and mulitply the last terms and you now have:
x^2+2x-x-2+x^2+5x-3x-15+x^3+7x^2+10x+13x^2+91x+130
Combine like terms on each side and you have:
2x^2+3x-17=x^3+20x^2+101x+130
Get all terms to the left side and you now have:
-x^3-18x^2-98x-147=0
from here use synthetic division or factor by grouping...hope this helped!